Dannii : My Style - Minogue, Dannii (London Simon & Schuster, 2011)
The definitive style guide for women who want to be fashionable, sexy and confident, by thewoman of the moment
Include Color Illustration
Keywords: Women's clothing -- Beauty, Personal -- Fashion